A COMEMORAÇÃO DO CENTENÁRIO DA IMPRENSA PERIÓDICA BRASILEIRA NO IHGB: UMA MEMÓRIA DO JORNALISMO NACIONAL (1908) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
The present dissertation has as scope a study of the memory and commemoration of the centenary of the press from the Revista do Instituto Histórico e Geographico Brazileiro (IHGB). The commemorative edition of the magazine IHGB aimed to elaborate a sort of complete inventory of all the newspapers published in the national territory until then. Each state would have one responsible for conducting the survey that would later be published in inventory format. According to the Institute, there were approximately 25,000 titles printed in the country during the first 100 years of the official press, however, approximately 5,000 newspapers were published and published in the form of catalogs. In this way, the focus of this study is the discussion about the commemoration of the centennial of the press through the Consecrated Tomo to the Commemorative Exhibition of the First Centenary of the Periodic Press in Brazil, as well as other regional editions produced by the IHGB, such as the states of Pernambuco, Paraná and São Paulo. In this case, the press as a fundamental vehicle in training for the written history and history of Brazil. The project designed by the Institute served as a review of the national and regional print production, and was a collective intellectual effort that thought the history of the Brazilian press. The present study also shows that Brazilian journalism has developed rapidly if it is taken into account that the printed word was only officially accepted in the country in the 19th century. The speeches of the intellectuals of the IHGB evaluated the press as an important factor of the country's progress, being this pretext more than relevant for the organization of the centenary.
Keywords: IHGB.; História do Brasil.; História da Imprensa; História da palavra impressa.; IHGB; History of Brazil. History of the Press; History of the printed word; CNPQ::CIENCIAS HUMANAS::HISTORIA